The Reality and Challenges of Authoritative Regulation on Hadith Publication in Malaysia and Indonesia - Bahrudin, Mohamad Khalid; Suliaman, Ishak; Mohamed Adnan, Mohamad Azrien (Jurnal Usuluddin, 2023)
Dissemination of inauthentic hadith in publications, ill-intent understanding of hadith text and its exploitations for personal or group interests are some of the contemporary issues faced by Malaysia and Indonesia. This article focuses on the reality and challenges of authoritative regulation on hadith publication in both countries to tackle afro mention issues. This phenomenological study uses interviews, observations and document analysis as data collection methods. This study discovered that regulation mechanism is implemented in Malaysia in the form of guidelines issued by federal authorities. These guidelines, however, are not backed up by stern and clear enforcement by the government. At the state level, there are enactments gazetted but they are too broad in their interpretation and more to the context of maintaining hadith chastity from contemptuous acts. On the other hand, Indonesia at the federal level, does not have any specific and systematic methods to regulate the text of hadith and, at the moment, only depends on available general mechanisms especially the one applied in higher education institutions. The study concludes, in order to preserve hadith corpus from a faulty utilization and abusive application, both governments should pay more attention in introducing new laws as well as strengthening existing mechanism related to hadith text in this archipelago.